PENGARUH SUKU BUNGA DAN NILAI TUKAR TERHADAP RETURN SAHAM MELALUI STRUKTUR MODAL - jurnalpps pps; Ratna Dwi Hayuningtyas; Nugroho Mardi Wibowo; Chandra Kartika (Jurnal Manajerial Bisnis, 2020)
This study aims to manifest empirically is there an effect of interest rates and exchange rates on stock returns with capital structure. This study employs mainly a quantitative approach to support in the data analysing. The research data is secondary data. The data collection is from documentation. The population of this study is food and beverage sub-sectors listed in Indonesia Stock Exchange 2014 - 2018 period with the sampling technique uses purposive sampling method, they are amount of 12 samples of the company. The data analysed is used analysis path. These results of this study were interest rates did not have effect on capital structure, the exchange rates did not have effect on capital structure. While, interest rates had a negative effect and significant on stock returns, the exchange rates had a negative effect and significant on stock returns, the capital structure had a positive effect and significant on stock returns. The results also got that interest rates did not have an indirect effect on stock returns with capital structure and exchange rates had a negative effect and significant on stock returns with capital structure.Keywords: interest rates, exchange rates, stock return, capital structure